The Emperor has no clothes (Actualizaciones en Sida e Infectología, 2021)
Almost two centuries ago, in 1837, Hans Christian Andersen published a fable entitled The Emperor's New Clothes. The story goes that a monarch who was very concerned about his wardrobe one day heard that a couple of craftsmen could make him the lightest cloth he could imagine, but, moreover, with the suggestive feature that it was invisible to anyone who was foolish or incompetent. Once they informed him that the clothes were "finished" (and unwilling to admit that he couldn't see anything), the Emperor put on the non-existent outfit made from the cloth to participate in a parade and walked around in front of everyone in his underwear until one boy exclaimed: “But the Emperor has no clothes!”Today science is the one without clothes. As never before, a microorganism that is 800 times smaller than the diameter of a hair (one tenth of a micron) and unleashed a pandemic at the end of last year that is threatening health systems, societies and economies all over the planet, took the clothes off the machinery of knowledge that built the world as we know it and exposed, to everyone's eyes, those gears that combine certainty and uncertainty at the same time.Paradoxically, after having promoted to the public the leading image of the physician and the idea that science has the answer to everything, this year we journalists who work on these topics were faced with the task of showing lay people the behind-the-scenes of scientific work, the advances and setbacks, the proofs and refutations, the controversies and dissent that are our daily bread for experienced specialists, but have rarely been exposed to those who do not visit laboratories or participate in congresses dedicated to discussing advances in medicine.Thus, we found ourselves discarding the convenience of wearing a mask and then endorsing the imperative need not to forget it when leaving home, or assuring that the virus is too big to be left floating in sprays and then warning that it could remain suspended in the air for one to two hours, just to mention two cases in which we had to retrace our steps and deny what we had assured some time before. Of course, that's how science works, on the best available evidence, but many didn't know that... "Copernican shifts" used to happen in the span of decades, and today they happen week by week.There is probably no information more difficult to convey than the lack of answers or provisional truths. If we add to this the divergent criteria on the most effective measures to control the circulation of the virus (restrictions vs. openings, testing symptomatic vs. asymptomatic, among others), the conflicts of interest, desperation and unrestricted circulation of false truths that took social networks by storm in which a democratic anonymity put authorities in their fields of study on an equal footing with charlatans (a group that sometimes even included renowned scientists!), the challenge is enormous.Someone said that the pandemic battle would be won in the laboratory. I beg to differ: the pandemic is not merely a biological fact, but also a sociological, cultural and economic one. And in this scenario, communication and its spokespersons, both physicians and journalists, play a leading role. Hopefully, we will be able to meet the demands of the moment.